2014
DOI: 10.1098/rsif.2013.0851
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear light-sheet fluorescence microscopy by photobleaching imprinting

Abstract: We present a nonlinear light-sheet fluorescence microscopy (LSFM) scheme based on photobleaching imprinting. By measuring photobleaching-induced fluorescence decay, our method simultaneously achieves a large imaging field of view and a thin optical section. Furthermore, the scattered-lightinduced background is significantly reduced, considerably improving image contrast. Our method is expected to expand the application field of LSFM into the optical quasi-ballistic regime, enabling studies on non-transparent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…sub-diffractio llular imaging per-resolution yes, making su convolution m ratio [14]. M can be pot SFM) [16] …”
Section: Resultsmentioning
confidence: 99%
“…sub-diffractio llular imaging per-resolution yes, making su convolution m ratio [14]. M can be pot SFM) [16] …”
Section: Resultsmentioning
confidence: 99%
“…Zebrafish husbandry was described in our previous work [21]. All animal work was performed in compliance with Washington University’s institutional animal protocols.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorophores irreversibly lose their ability to fluorescence due to the photon-induced chemical damage and covalent modification. The photobleaching obeys an empirical exponential temporal decay law (Gao et al, 2014b) (shown in Figure 2A) and in the Nth frame captured at time t n , the absorption rate µ is also a function of t n , written as:…”
Section: Photobleaching Imprinting Of Ltfmmentioning
confidence: 99%